Pigmented Superficial Basal Cell Carcinoma of the Nipple-Areola Complex: A Case Report - Xinru Chen; Na Zhang; Hongping Ge; Xiaoli Zhai; Meiyan Wang; Min Zhang (Case Reports in Dermatology)
Introduction: Basal cell carcinoma (BCC) is the most common type of skin malignancy, accounting for approximately 80% of all non-melanoma skin cancers (NMSCs). Ultraviolet (UV) exposure is a significant risk factor for BCC development, which typically occurs in sun-exposed areas. BCC arising in non-sun-exposed regions, such as the nipple-areola complex (NAC), is exceedingly rare, with fewer than 100 cases reported globally. This report describes a case of pigmented superficial BCC in the NAC of a 76-year-old Asian woman. Case Presentation: A 76-year-old Asian female presented with a 5-year history of a slowly enlarging lesion on her left breast, with recent rapid growth. Physical examination revealed a 10 mm × 8 mm blue-gray, pearl-like plaque on the NAC. Histopathology confirmed pigmented superficial BCC. Preoperative imaging, including breast ultrasound, chest computed tomography (CT), SPECT-CT, and axillary lymph node ultrasound, showed no evidence of metastasis. The patient underwent standard surgical excision with a 10 mm margin, followed by pathologic evaluation, confirming clear margins. The patient was discharged on the second postoperative day and remained asymptomatic at a 3-month follow-up. Conclusion: Pigmented superficial BCC of the NAC is an uncommon presentation due to the area’s minimal sun exposure and lack of pilosebaceous units. This case underscores the importance of considering BCC in non-sun-exposed areas, particularly in elderly patients. While nonsurgical options such as photodynamic therapy may offer superior esthetic outcomes, the patient’s financial constraints led to the selection of a cost-effective surgical excision, which successfully eliminated the tumor.